Efeito antioxidante, hepatoprotetor e genoprotetor da geoprópolis da abelha partamona cupira produzida no semiárido nordestino - Costa, Kizzy Millenn de Freitas Mendonça (2018)
Hepatic pathologies are among the world's greatest health problems. Thus, there is a growing interest in studies related to the hepatoprotective effect of natural products, objectifying develop new drugs in order to increase the chances of greater efficiency and to offer a variety of medicines. With a complex chemical composition and rich in phenolic compounds, the propolis produced by Partamona cupira exhibits a large spectrum of biological activities, among them the high antioxidant activity stands out, with notable anti-inflammatory, antibacterial and antineoplastic effects. Some studies show that just like propolis produced by bees of the Apis genus, the propolis produced by indigenous stingless bees also has high biological activity. Therefore, the objective of the present study was to evaluate the hepatoprotective effect of the hydroethanolic extracts of the geopropolis produced by the cupira bee (Partamona cupira), obtained from the beekepers of the semiarid region of Rio Grande do Norte. For that, the chemical composition and antioxidant activity of the propolis were evaluated; as well as the hepatoprotective potential, through the induction of experimental cirrhosis in rats; and also to the in vitro evaluation of the antineoplastic potential of propolis in a human hepatic carcinoma (HepG2) cell line, and as the potential genotype in normal fibroblasts cell line (L929) exposed to hydrogen peroxide (H2O2). The samples from geopropolis presented 20 phenolic compounds, being phenols and flavonoids. The geopropolis extract of the cupira bee did not show cytotoxicity in normal cells and showed antigenotoxic or genoprotective effect, with percentages of genotoxicity reduction of 92.2%, 74.5% and 46.1%, respectively, for the concentrations of 500, 250 and 100μl / mL of the extract. The results of serum levels of hepatic injury indicative enzymes, indicated that the hydroalcoholic extract of the geopropolis of the cupira bee did not cause hepatic toxicity and had a hepatoprotective effect against the hepatic injury induced by thioacetamide (TAA). Through the macroscopic and histological evaluation of livers, it is also possible to suggest that the extract of the propolis analyzed exerted a hepatoprotective effect on the severity of cirrhosis, since in the livers of the animals treated with extract it was possible to verify that the regenerative nodules characteristic of cirrhosis were smaller and more discrete, when compared to the animals of the cirrhotic group. Likewise, there was a significant reduction in the percentage of collagen in the treated group compared to the cirrhotic group, demonstrating the hepatoprotective effect of the geopropolis of the honey bee, which was able to reduce the damage to the hepatocytes, although no statistical difference was observed in the weight of the livers in these groups, the stereological analysis showed that there was a significant difference in the percentage of hepatocytes and collagens among these groups. Thus, it is concluded that the extract of the geopropolis of the cupira bee presents varied chemical composition and promising pharmacological activities, highlighting the antioxidant, non-cytotoxic, genoprotective and hepatoprotective, since it exerted a hepatoprotective effect through the hepatic lesion induced by thioacetamide